Ética na capelania universitária - Lima, Edivaldo Lopes de (2014)
The master thesis deals with ethics in university chaplaincy. Ethics is essential in human relationships and is present in all spheres of human life. It is not different in academic settings. Professional ethics grounds the practice of the university chaplaincy professional in his/her professional practice. Throughout the work it was noticed that although the institution follows Christian precepts, the ethos of which is based on the principles of love, community living, the otherness, care, freedom with responsibility, professional ethics ultimately incorporates such values, since being ethical is to act based on socially constructed and accepted principles.. It was found that interpersonal relationship between the university chaplain and the individual is based on trust, allowing for open communication between them, but secretive. Thus, the university chaplaincy, with a caring role, becomes a ministry of help and pastoral care.